Unusual Presentation of Polyautoimmunity and Renal Tubular Acidosis in an Adolescent With Hashimoto's Thyroiditis and Central Pontine Myelinolysis - Bruns, Nora; Finkelberg, Ilja; Al-Attrach, Ibrahim; Hoyer, Peter F.; Büscher, Rainer (Frontiers in Endocrinology, 2020)
Background: Hashimoto’s thyroiditis is frequently associated with other autoimmune diseases and may include renal involvement. Case description: A 17-year-old female with previously diagnosed Hashimoto’s thyroiditis and vitiligo was admitted to a pediatric intensive care unit with hypokalemic paralysis and acidosis, after having suffered from recurrent muscular weakness for approximately one year. A few days later she developed central pontine myelinolysis. After initial stabilization she was also diagnosed with distal renal tubular acidosis (dRTA) and tubular proteinuria which can occur in Sjögren’s syndrome. Extended screening for autoimmune diseases additionally revealed celiac disease. Treatment with Prednisone and substitution of potassium quickly lead to the resolution of proteinuria and dRTA, but unilateral paralysis of the sixth nerve as a result of central pontine myelinolysis was irreversible. Conclusions: This is the rare case of polyautoimmunity including autoimmune thyroiditis, Sjögren’s syndrome, vitiligo and celiac disease in an adolescent with few disease-specific symptoms. The diagnoses were made via a complicating nephritis causing dRTA and proteinuria. Delay in diagnosis lead to permanent neurological damage. This case highlights the need for pediatricians to be aware of rare accompanying diseases and their complications in “common” pediatric autoimmune diseases like Hashimoto’s thyroiditis and celiac disease.